Wymagania i zadania controllera i specjalisty ds. benchmarkingu w przedsiębiorstwie - Kowalak, Robert (Controller and Benchmarker in Organisational Structure of Company, 2009)
This article presents functions and tasks of controller and benchmarker in companies. The controller is a more important person in an enterprise and has more spectrum of decisions. A benchmarker gives him information to prepare decisions for managers. This article presents also the relationship between a controller and a benchmarker in organizational structure of enterprise. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 45-49